1988
DOI: 10.1161/01.res.62.6.1175
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin biosynthesis and phospholipase activity in hypoxic rat myocardium.

Abstract: Phospholipid metabolism was studied in rat myocardial slices that were incubated under normoxia or hypoxia for up to 24 hours. Phospholipid degradation was prominent in hypoxic myocardium, particularly phosphatidylcholine, which markedly decreased after 24 hours of hypoxia. In contrast, lysophosphatidjlcholine increased. The mechanism of phospholipid degradation in hypoxic myocardium was studied. The highest activity for phospholipase A 2 among subcellular fractions was found in microsomal fraction. In hypoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…One explanation could be the activation of phospholipases by hypoxia, resulting in an increased degradation of phospholipids (23,24). During the first 3 h of hypoxia more prostaglandin I 2 was released than in the following 21 h. Similar results were obtained by Palluy et al (25) and also by Farber et al (26), who suggest a transient activation of cyclooxygenase by hypoxia.…”
Section: Discussionsupporting
confidence: 77%
“…One explanation could be the activation of phospholipases by hypoxia, resulting in an increased degradation of phospholipids (23,24). During the first 3 h of hypoxia more prostaglandin I 2 was released than in the following 21 h. Similar results were obtained by Palluy et al (25) and also by Farber et al (26), who suggest a transient activation of cyclooxygenase by hypoxia.…”
Section: Discussionsupporting
confidence: 77%
“…In patients with acute myocardial infarction, elevation of the serum FFA level and increased catecholamine secretion have been reported [1]. We have also reported that FFA and PGI 2 are released by hypoxic perfused rat hearts [2] and have demonstrated that increased FFA and PGI2 are caused by enhanced phospholipase A 2 [3]. Kurien and Oliver first reported the existence of a relationship between high serum FFA concentrations and serious arrhythmias and/or death in patients with acute myocardial infarction [4].…”
Section: Introductionmentioning
confidence: 76%
“…PLA2 activity was increased in homogenates of small intestinal mucosal cells after ischemia and reperfusion (34). Kawaguchi and Yasuda (39) reported increases of mitochondrial and microsomal PLA2 activity in hypoxic myocardium. This PLA2 activity had a substrate specificity for PE, but the mechanism of activation was not clarified and the enzymatic activity was not further characterized.…”
Section: Introductionmentioning
confidence: 98%